Job burnout syndrome and stress coping strategies of academic students - Wilczek-Rużyczka, Ewa; Jabłeka, Magdalena (Polish Journal of Public Health, 2013)
Introduction. People focused on helping others in their daily professional career are especially exposed to stress. The inability to relieve stress is a common cause of the burnout syndrome. It turns out that also college students, who are prepared to work with people, are exposed to the job burnout syndrome, even during their education process. The possible cause might be unfamiliarity with effective stress coping methods or inability to use them properly.Aim. The aim of this paper is to study job burnout syndrome and stress coping strategies among students of selected academic majors, and also to analyze relations and differences between these results.Material and methods. The research has been conducted among 141 fifth or sixth-year students of nursing, medicine and pedagogy in Krakow. The study was based on surveys: a questionnaire made by the author, The Maslach Burnout Inventory (MBI) and The Coping Inventory for Stressful Situations (CISS).Results. The analysis of obtained results has showed that there is a significant difference between stress coping strategies among examined students and that there is a relation between job burnout syndrome and students’ academic majors. There is also a relation between job burnout and stress coping strategies among students of selected academic majors. However, there is no relationship between job burnout and students’ selected academic majors.Conclusions. There is also a relationship between students’ stress coping strategies and selected academic majors and burnout syndrome.